INFLUENCE OF BIOFOULING ON THE OYSTER SETTLEMENT IN THE VICINITY OF A POWER STATION, INDIA - Sasikumar, N; Nair, K V K; Azariah, Jayapaul (Indian Journal of Fisheries, 2011)
Settlement studies on Crassostrea madrasensis were made using exf)erimental test panels (15x10 cm) suspended at various depths (1^,5 and 7m) from Madras Atomic Power Station jetty. The species showed continuous settlement throughout the year with two maxima; one in April and the other in October. While the species showed maximum growth rates at the intake filter gate, growth rates were relatively low at the condenser outfall of the power station possibly due to the altered environmental conditions at the latter location. Survival rate of C. madrasensis was relatively low on panels having green mussel and barnacle settlement as compared to those panels free of these foulants. The paper discusses the importance of biofouling assessment in selection of suitable sites for coastal aquaculture.